LEGAL PROTECTION FOR CONSUMERS BUYING AND SELLING USED IMPORTED CLOTHES (CAKAR BONGKAR) ACCORDING TO LAW NUMBER 8 OF 1999 CONCERNING CONSUMER PROTECTION - Annisa Nurlia Mamonto, Andi; Tuharea, Farida; Ibrahim, Nanang; Asmi, Nurul; Kusuma Irjananta, Rama (JOURNAL EQUITABLE, 2026)
This study examines the legal protection of consumers in the practice of buying and selling imported secondhand clothing (commonly known as cakar bongkar) within the framework of Indonesian law. The research employs a normative juridical method with a statutory and conceptual approach, focusing on the analysis of Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen and related regulations governing trade and consumer rights. The findings indicate that, in principle, the sale and purchase of secondhand goods are legally valid under civil law, provided that the transaction fulfills the essential requirements of a valid agreement, including consent, legal capacity, a specific object, and a lawful cause, as stipulated in Kitab Undang-Undang Hukum Perdata. However, such transactions must also adhere to transparency principles, particularly in providing accurate and honest information regarding the condition of goods. Furthermore, the study reveals that the circulation of imported secondhand clothing is explicitly prohibited under Undang-Undang Nomor 7 Tahun 2014 tentang Perdagangan and Peraturan Menteri Perdagangan Nomor 40 Tahun 2022, due to concerns related to consumer safety and the protection of domestic industries. Consumers are entitled to legal remedies, including compensation and dispute resolution mechanisms, when they suffer losses due to defective or harmful products. Nevertheless, legal protection becomes limited when consumers knowingly engage in transactions involving prohibited goods. Therefore, effective consumer protection requires not only comprehensive regulations but also consistent law enforcement, government supervision, and increased legal awareness among both business actors and consumers.